Psychological Well-being Character with Anterograde Amnesia in the Film Even if This Love Disappears From the World Tonight - Ramadhani, Athaya Anargya Dwi; Afda, Muhammad Wildan Sidqi; Noviana, Fajria (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
Psychological well-being focuses on positive functioning, happiness, and life satisfaction. Various countries have made efforts to raise awareness among the public about the importance of well-being through various media, one of which is film. Therefore, this paper focuses on psychological well-being through the lens of the film Even if This Love Disappears From the World Tonight , which matches well with targets in Sustainable Development Goals (SDGs) Goal 3: ensure healthy lives and promote well-being for all at all ages. This study delves into the character of Maori Hino, who grapples with anterograde amnesia, using Carol Ryff's six dimensions of psychological well-being as a framework. This qualitative literary research used the psychology of literature design. The analysis found five dimensions of psychological well-being: self-acceptance, positive relations with others, purpose in life, autonomy, and personal growth. The results of this study concluded that those five dimensions indicate the psychological well-being of Maori Hino. Even though she faces complicated challenges, the support from people around her significantly improves her well-being. These findings highlight the importance of self-acceptance and social support in achieving psychological well-being.
Keywords: psychological well-being, anterograde amnesia, film analysis, Carol Ryff, Even if This Love Disappears From the World Tonight